Alterações na medula óssea de pacientes com doenças autoimunes sob tratamento com imunossupressores - Costa Filho, José Djandir (2014)
Treatment related Myelodisplastic syndrome (MDS-t) is a clinical disease described as complication of cytotoxic therapy. Its occurrence depends on the mechanism of DNA damage, cumulative dose or intensity of the preceding cytotoxic therapy. Immunosuppressant drugs used in autoimmune diseases have been linked to the development of MDS-t in series and case reports. Antimetabolites like methotrexate (MTX) and Azathioprine (AZA) have been related to that disease. OBJECTIVES: to evaluate bone marrow abnormalities in subjects with under treatment with MTX and AZA that developed cytopenias. METHODS: bone marrow smear, karyotype and peripheral blood analyses were performed in 24 subjects with permanent or transient cytopenias in use of MTX (and combinations) and AZA. RESULTS: Sixteen subjects (66%) have rheumatoid arthritis (RA) and one (4%), psoriatic arthritis (PsolRA). They were treated with MTX alone or in combination with leflunomide, abatacept and infliximab. Five (20%) subjects have Systemic Lupus Erythematosus (SLE). Sjögren Syndrome (SS), Neuromielits optica (NMO) and Miastenia Gravis (MG) were each one represented by one subject (4% each). Blood transfusions (red cells and platelets) were required in 9 (37%) of subjects and 8 (33%) have clinical important infections. Death occurred in 2 (8%) subjects due infections followed by sepsis). There was not statistical significant difference between the groups in use of MTX and AZA for blood transfusion and occurrence of infections. In both MTX and AZA group, anemia was the was the most common find, verified in 59% (13) subjects in use of MTX and 85,7% (6) in use of AZA. Bicytopenia and pancytopenia was also found in both groups in more than 10% of cases. Association of leflunomide to MTX treatment did not resulted in statistical difference in peripheral blood counts when compared to MTX alone. Moderate dysplasia was found in 29,4% (5) in subjects. Erythroid dysplasia was the most frequent result. Leucopenia e lymphopenia had statistical association with moderate dysplasia in bone marrow smear (Med leuc = 6200 (12630-3778);p = 0,0023 AND Med linf = 1964 (3929-833); p = 0,0006). Karyotype aberration was verified in one case, described as interstitial deletion in chromosome 5 long arm although his bone marrow was normoplasic. Dysplastic abnormalities were found in 42,8% (3) of subjects in use of AZA. Once more erythroid dysplasia was the most frequent result. Statistical significance was not found among cytopenias and dysplastic abnormalities in bone marrow smear. Karyotype aberration was verified in 2 cases. One of them had interstitial deletion in long arms of chromosomes 5 and 7 (46,XX,del(5)(q31q33),del7(q32)[4]). The other one, in chromosome 17 short arm (46 XX del(17)(p11.2) [3]). CONCLUSIONS: leucopenia and lymphopenia can predict, in such level, the presence of marrow toxicity. Karyotype aberration was an unpredictable found and requires a close following once the prognostic of this condition is not known, given the risk of hematologic neoplasms, such as MDS-t.